Sosialisasi dan Pendampingan Implementasi Peraturan Gubernur DIY No. 60 Tahun 2020 bagi Guru PPKn MGMP SMA dan SMK Kabupaten Kulon Progo - Sumaryati Sumaryati; Trisna Sukmayadi (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Corruption, even during a pandemic, is still happening. This means that preventing corruption and corrupt behavior must be more massive, likewise with the implementation of Anti-Corruption Education (PAK). The Governor of the Special Region of Yogyakarta issued the Governor of DIY Regulation No. 60 of 2020 concerning the Implementation of Anti-Corruption Education Insertions in High Schools and Vocational High Schools and Special Schools. This regulation is not yet known and understood by PPKN teachers in general and PPKn teachers in SMA and SMK in particular. Consequently, the joint commitment in implementing the PAK has not been developed. Based on this, the Service Team carried out socialization and assistance to implement the Gubernatorial Regulation to PPKn SMA and SMK teachers in Kulon Progo. The activity is carried out in three stages, preparation, implementation, and monitoring evaluation—the method with a participatory approach. The service output is a set of learning tools for PPKn SMA and SMK Class X subjects containing PAK. The impact of the activities included PPKn teachers who knew and understood PPKn with PAK content, were skilled at finding and compiling learning media, and were skilled at collecting PPKn learning tools with PAK.